Too many big fish in a small pond? The nexus of Overqualification, job satisfaction, job search Behaviour and leader–member exchange - Kengatharan, N. (My University, 2020)
Drawing on the theories of person–job fit, relative deprivation, work adjustment and reasoned action, the present study aims to investigate the nexus of perceived overqualification, leader–member exchange (LMX), job satisfaction and job search behaviour. Anchored in philosophical assumptions, the present study adopts a survey research strategy with a cross-sectional time horizon. Data were garnered with a self-reported questionnaire from 607 convenience-sampled employees working in state-owned organisations in Sri Lanka. The study found a significant negative relationship between perceived overqualification and job satisfaction. The results further revealed that LMX moderates the negative relationship between perceived overqualification and job satisfaction such that the negative relationship is weaker at a high quality LMX. No less importantly, the results disclosed that job satisfaction is a complementary mediator of the relationship between perceived overqualification and job search behaviour. The study contributes to the frontiers of HRM literature and provides useful practical implications.
Keywords: Job satisfaction; Job search behaviour; Perceived overqualification; Person-job fit theory